Factors Associated with Antiretroviral Therapy Adherence in Patients with HIV at a Public Hospital in Central Jakarta, Indonesia - Fatimah, Kareena Sari; Hanifah, Laily; Simanjorang, Chandrayani; Fithri, Nayla Kamilia (UI Scholars Hub, 2026)
Patients with human immunodeficiency virus (HIV) are required to take antiretroviral therapy (ART) to suppress the virus. However, suboptimal adherence remains a critical barrier that can lead to treatment failure and persistent transmission risks. This study aimed to identify factors associated with ART adherence in patients with HIV. This quantitative study with a cross-sectional design consisted of patients with HIV aged >18 years who received care at the voluntary counseling and testing clinic of a public hospital in Jakarta, Indonesia. Purposive sampling was used. This study used HIV care and ART overview forms as instruments. Data were analyzed using multiple logistic regression. The results showed that among 266 patients with HIV, 213 (80.1%) reported adherence to ART. This study found that age ≥44 years (adjusted POR 2.631; 95% CI 1.059–6.533), higher education level (adjusted POR 4.407; 95% CI 1.948–9.973), and CD4 count ≥200 (adjusted POR 2.593; 95% CI 1.219–5.517) were associated with higher adherence. Conversely, patients with an ART duration of 1–5 years (adjusted POR, 0.259; 95% CI, 0.100–0.673) and those who had never experienced drug side effects (adjusted POR, 0.108; 95% CI, 0.014–0.860) were less likely to be adherent. The dominant factor was the experience of drug side effects, suggesting that adherence should be enhanced through proactive counseling.